The influence of post treatments on the microstructure and corrosion behavior of thermally sprayed NiCrMoAl alloy coating - P. Daram (2020)
© 2020 Elsevier B.V. The relationship between microstructure and corrosion behavior of arc-sprayed NiCrMoAl alloy coating after different post treatments has been studied. Two different post treatments were applied to improve the properties: heat treatment at 1100 °C for 60 min and flame remelting. The microstructural characteristics of the as-sprayed and post-treated coatings were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD) and transmission electron microscopy (TEM). The corrosion behaviors of all the coatings were also studied. The results reveal significantly different microstructure, including morphology, distribution and percentage of the phases, in the different coatings. For both post-treated coatings, intermetallic compounds (MoSi2, MoNiSi, and topologically close-packed (TCP) phases) around γ-Ni phase were observed. Moreover, the microstructure of post-treated coatings contained more oxide phases at intersplat boundaries, leading to a decrease in the porosity after post treatments. Due to the microstructural change after post treatments, the corrosion rate was decreased. A decrease of open pores along with an increase of oxide phases at intersplat boundaries, significantly contributed to enhancing the corrosion resistance of the thermally sprayed NiCrMoAl alloy coating.